2000
DOI: 10.1007/s004170050379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical povidone-iodine versus topical ofloxacin on experimental Staphylococcus keratitis

Abstract: Betadine 0.5% demonstrates a statistically significant bactericidal effect compared with untreated staphyloccocal keratitis in our experimental model. Ofloxacin has superior antibacterial effect under the conditions studied. Further improvements in the povidone-iodine formulation are warranted prior to consideration for human keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…In agreement with the present study Gregori et al compared the effect of 5 % povidone iodine with placebo drops (one drop of each,10 minutes before antibiotic treatment) in the treatment of corneal ulcer, and they concluded that the effect povidone iodine has no effect in reducing the number of bacteria on the cornea (13). In agreement with the present study Melki et al compared the effect of 0.5 % and 10 % povidone iodine with ofloxacin 0.3 % on 21 rabbit eyes for a period of eight hours, and revealed that although 0.5 % povi-done iodine has a greater bactericidal effect compare to the untreated cases, but however, its effect is less than ofloxacin (14). Michalova et al studied the effect of 5 % povidone iodine on Pseudomonas infectious keratitis in rabbits for 24 hours, and claimed that povidone iodine is not effective against Pseudomonas, which was similar to the present study; although it was another infectious organism (15).…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with the present study Gregori et al compared the effect of 5 % povidone iodine with placebo drops (one drop of each,10 minutes before antibiotic treatment) in the treatment of corneal ulcer, and they concluded that the effect povidone iodine has no effect in reducing the number of bacteria on the cornea (13). In agreement with the present study Melki et al compared the effect of 0.5 % and 10 % povidone iodine with ofloxacin 0.3 % on 21 rabbit eyes for a period of eight hours, and revealed that although 0.5 % povi-done iodine has a greater bactericidal effect compare to the untreated cases, but however, its effect is less than ofloxacin (14). Michalova et al studied the effect of 5 % povidone iodine on Pseudomonas infectious keratitis in rabbits for 24 hours, and claimed that povidone iodine is not effective against Pseudomonas, which was similar to the present study; although it was another infectious organism (15).…”
Section: Discussionsupporting
confidence: 91%
“…The open-label pilot human study by Pelletier et al 16 documented the efficacy of this new formulation of ophthalmic suspension containing povidoneiodine 0.4% dexamethasone 0.1% in the treatment of adenoviral keratoconjunctivitis. This small, open-label human clinical trial was conducted in light of the extensive ophthalmic use of these two drugs: povidone-iodine [19][20][21][22][23][24][25][26] and dexamethasone. 10,[16][17][18] After the study by Pelletier et al 16 was published, Clement et al 29 published results on tests on rabbit corneas and showed that povidone-iodine 0.4% dexamethasone 0.1% was the most effective agent in minimizing the clinical signs of adenovirus infection in rabbit eyes when the treatment was compared to cidofovir 0.5%, tobramycin/dexamethasone ophthalmic suspension and balanced salt solution.…”
Section: Discussionmentioning
confidence: 99%
“…10 Povidone-iodine is an antiseptic extensively used in preparation for general surgery, for ophthalmic purposes and for laboratory disinfection. [19][20][21][22][23][24][25] Diluted povidone-iodine solutions inhibit numerous viruses, bacteria, fungi and some other parasites. 26 Previously studies have shown that povidone-iodine is a potential option for reducing contagiousness in cases of adenoviral infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, a randomised controlled trial assessing a single 10 min povidone-iodine instillation before corneal scrape in patients presenting with bacterial keratitis did not reveal a statistically significant difference between the pre- and postinstillation load of pathogen 34. In the povidone-iodine form, the majority of iodine is in the non-toxic stable tri-iodide form 35. Free iodine is a strong oxidising agent of the functional groups of amino acids, nucleotides, and unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%